Multi-Objective Planning Research on Micro Energy Network Considering Desalination. (February 2019) - Liu, Weikang; Wang, Dan; Yu, Xiaodan; Wang, Weiliang; Lan, Yu; Wang, Xudong; Yu, Jiancheng
Abstract: With the rapid development of economy, the lack of freshwater resources has become increasingly urgent in many areas of China. Desalination can ease some of the pressure on freshwater supply, especially in coastal areas and isolated islands. The micro energy network is an efficient distributed energy supply system that can be used to supply electricity, cooling, heat and freshwater simultaneously. In this paper, wind turbine, photovoltaic(PV), combined cooling, heating and power(CCHP) system and desalination unit are integrated into the micro energy network. A multi-objective optimization research is conducted on the key equipment capacity and the operation of the desalination unit, with the goal of optimizing the life cycle cost and annual CO2 emissions simultaneously. And through the study of cases, the impact of the operation of desalination unit on the planning solutions of micro energy network is researched.